"The Mother Is a School" Muslim Mothers and their Religio-Educative Roles - Hamed, Sara (Journal of the Motherhood Initiative for Research and Community Involvement, 2017)
Based on my 2014 master’s ethnographic study, this article examines how my research question changed from “What role does Muslim mothering play in Islamic education?” to “How do Muslim mothers of the GTA imagine their religio-educative roles?” I examine how the seemingly empowering adage “the mother is a school” is actually a burdensome ideology. I locate spiritual growth in the interplay of remembrance, forgetfulness, and repentance, which are indisputable parts of the discursive backdrop against which my participants imagine what it is to be Muslim. Using found poems constructed from interviews with participant mothers, I use the themes of time and translation to highlight their overwhelming feelings of failure to mother adequately. Along with the mothers’ feelings of failure, I identify their moments of fleeting success as the important work of translating impersonal religious knowledge into personal experiences that are meaningful to their children. To move beyond the school metaphor, I offer “poetic spaces”—the spaces where my participants navigate creative and transformative relationships with a discursive tradition that is largely produced without them. Including myself as a Muslim mother, I identify my own poetic space as a site for resistance and look forward to creating alternative metaphors to reimagine mothering in the context of Islam.